The Challenges Facing the Saudi Family in Achieving the Values of Digital Citizenship - Al-Azzam , Seham Mohammed (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to identify the challenges facing the Saudi family in achieving the values of digital citizenship, which are represented by the values of digital respect, digital knowledge, and digital protection. This study focuses on the challenges faced by families in attaining these digital citizenship values, with the hope that specialists, experts, practitioners, and individuals interested in family issues will find guidance to develop plans and proposals for overcoming these challenges. Methods: The social survey method was used with a simple random sample, reaching 335 female employees at the Imam Mohammad Ibn Saud Islamic University in Riyadh. The data were collected using a questionnaire tool during the period from 10/4/1442 AH to 10/5/1442 AH. Results: Several findings have been reached, the most important of which is that the Saudi family faces many challenges in achieving the values of digital citizenship, which are represented by digital respect, digital knowledge, and digital protection, all of which have a moderate degree. Conclusions: The study reveals several recommendations, the most important of which is the development of an integrated national plan to provide community members with the necessary skills to achieve the ideals of digital citizenship.